Bacterial outer membrane vesicles bound to bacteriophages modulate neutrophil responses to bacterial infection - Pennetzdorfer, Nina; Popescu, Medeea C.; Haddock, Naomi L.; Dupuy, Fannie; Kaber, Gernot; Hargil, Aviv; Johansson, Patrik K.; Enejder, Annika; Bollyky, Paul L. (Frontiers in Cellular and Infection Microbiology, 2023)
Pseudomonas aeruginosa is a major human pathogen, particularly effective at colonizing the airways of patients with cystic fibrosis. Bacteriophages are highly abundant at infection sites, but their impact on mammalian immunity remains unclear. We previously showed that Pf4, a temperate filamentous bacteriophage produced by P. aeruginosa, modifies the innate immune response to P. aeruginosa infections via TLR3 signaling, but the underlying mechanisms remained unclear. Notably, Pf4 is a single-stranded DNA and lysogenic phage, and its production does not typically result in lysis of its bacterial host. We identified previously that internalization of Pf4 by human or murine immune cells triggers maladaptive viral pattern recognition receptors and resulted in bacterial persistence based on the presence of phage RNA. We report now that Pf4 phage dampens inflammatory responses to bacterial endotoxin and that this is mediated in part via bacterial vesicles attached to phage particles. Outer membrane vesicles (OMVs) are produced by Gram-negative bacteria and play a key role in host pathogen interaction. Recently, evidence has emerged that OMVs differentially package small RNAs. In this study, we show that Pf4 are decorated with OMVs that remain affixed to Pf4 despite of purification steps. These phages are endocytosed by human cells and delivered to endosomal vesicles. We demonstrate that short RNAs within the OMVs form hairpin structures that trigger TLR3-dependent type I interferon production and antagonize production of antibacterial cytokines and chemokines. In particular, Pf4 phages inhibit CXCL5, preventing efficient neutrophil chemotaxis in response to endotoxin. Moreover, blocking IFNAR or TLR3 signaling abrogates the effect of Pf4 bound to OMVs on macrophage activation. In a murine acute pneumonia model, mice treated with Pf4 associated with OMVs show significantly less neutrophil infiltration in BAL fluid than mice treated with purified Pf4. These changes in macrophage phenotype are functionally relevant: conditioned media from cells exposed to Pf4 decorated with OMVs are significantly less effective at inducing neutrophil migration in vitro and in vivo. These results suggest that Pf4 phages alter innate immunity to bacterial endotoxin and OMVs, potentially dampening inflammation at sites of bacterial colonization or infection.